Fishing Community Empowerment: An Effectiveness Analysis of a Fishing Gear Assistance Program in Palewai Village - Hidayat, Rahmat; Zahratunnisa, Fatimah; Azis, Laode Asrun; Amalia, Dea Rizky (SIGn Journal of Social Science, 2024)
Community empowerment programs often encounter implementation gaps at the local level, resulting in their failure to achieve their primary objectives. This research aims to conduct an in-depth analysis of the effectiveness of a fishing gear assistance program in Palewai Village, which exhibited contradictory results on the ground. Employing a qualitative case study approach, data were collected through in-depth interviews, observations, and document analysis, and were subsequently analyzed using the interactive model developed by Miles, Huberman, and Saldaña. The findings reveal that the program was fundamentally ineffective. The primary failure lay in an invalid targeting mechanism that relied on rigid administrative data, leading to both exclusion errors (deserving fishers received nothing) and inclusion errors (non-fishers received aid). This inclusion error even led to the sale of the aid by the mistargeted recipients. Ironically, amidst this distribution failure, a paradox of satisfaction emerged among recipients, driven by the high physical quality of the assistance. It is concluded that the program functioned more as a momentary charitable intervention than a transformative empowerment program, a failure rooted in design flaws that prioritized physical asset transfer over capacity building and monitoring.